Application of edible coatings in green plantain slices subjected to deep-fat frying (2015)
(Eng) Currently fried snacks are in great demand by Colombian consumers, however they have a high oil content, which reduces the life of the product and its sensory acceptability. An alternative to reduce the oil content, can be the use of hydrocolloids as edible coatings. Applying coatings of Guar gum, CMC and Xanthan gum at 1.2% was adequate to reduce the oil content by 43%, 31% and 23.34% respectively. Moreover, according to the implementation of the rotable central composite design for the Guar gum coating, the best operating conditions occurred at a guar gum concentration of 1.4% and a time of 90 seconds, when the banana slices undergo deep-fat frying conditions of 180 ° C and 3 minutes. Therefore, the coated plantain snack maintains a good quality with a low oil content, representing a more attractive product for consumers.